2009
DOI: 10.4137/cmped.s2224
|View full text |Cite
|
Sign up to set email alerts
|

IgA Nephropathy: A Twenty Year Retrospective Single Center Experience

Abstract: IgA nephropathy (IgAN) is a common glomerular disease whose etiology is unknown. Previous studies have described the clinical and laboratory features but none have specifically compared patients during different time periods. This 20 year retrospective study was performed to assess trends in the severity of IgAN from 1989–2008. We reviewed 57 patient charts that contained a confirmed biopsy diagnosis of IgAN and recorded data at the time of diagnosis and the final follow-up appointment. Clinical data included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…IgAN has been widely recognized since the 1970s [ 3 , 4 ] and previous studies have since improved clinical practices and reported useful treatment strategies for the disease, particularly the maximum usage of renin–angiotensin–aldosterone system (RAAS) blockers as a standard of care [ 5–8 ]. Although the understanding of the disease has advanced, there has been limited research investigating the time trends of characteristics and prognosis of IgAN with a sufficient number of patients [ 9 , 10 ]. As the population structure is changing and clinical guidelines have been developed [ 11 ], a study investigating whether any distinct features are present in the different time periods regarding IgAN may provide insights regarding future disease trends.…”
Section: Introductionmentioning
confidence: 99%
“…IgAN has been widely recognized since the 1970s [ 3 , 4 ] and previous studies have since improved clinical practices and reported useful treatment strategies for the disease, particularly the maximum usage of renin–angiotensin–aldosterone system (RAAS) blockers as a standard of care [ 5–8 ]. Although the understanding of the disease has advanced, there has been limited research investigating the time trends of characteristics and prognosis of IgAN with a sufficient number of patients [ 9 , 10 ]. As the population structure is changing and clinical guidelines have been developed [ 11 ], a study investigating whether any distinct features are present in the different time periods regarding IgAN may provide insights regarding future disease trends.…”
Section: Introductionmentioning
confidence: 99%